PELAKSANAAN FUNGSI MANAJEMEN SEKOLAH MENENGAH ATAS - kaja, Kaja (Universitas Kapuas Sintang, 2024)
School-based management is a school management system that grants authority and power to the institution to manage its operations in line with its potential, demands, and needs. A school is an institution that has the independent authority to establish educational programs (curriculum) and their implications for various school policies in accordance with the school's vision, mission, and educational goals. The aim of this study is to understand and analyze the functions of school management in Senior High Schools. The implementation of school management has been carried out through learning planning, learning implementation, and learning supervision. The learning objectives provide an overview of the relevance and activities to be carried out; the teaching and learning implementation is closely tied to the dimension of human resources, encompassing the number of teachers, educational qualifications, curriculum, library, and more. Furthermore, the supervision of teaching and learning is conducted by the principal in cooperation with the school’s teachers’ council, as well as by the Branch Office of Education both directly and indirectly. Therefore, the implementation of Senior High School Management functions can be concluded as a guideline for conducting learning activities to improve the quality of education. Additionally, alumni and the community should support teaching and learning activities as a form of participation in enhancing the quality of education.